KARAKTERISTIK KARAGENAN SEMI-MURNI DARI RUMPUT LAUT Kappaphycus striatum DAN Kappaphycus alvarezii - Lalu Danu Prima Arzani; Tjahja Muhandri; Nancy Dewi Yuliana (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2020)
Kappaphycus striatum and Kappaphycus alvarezii are kappa carrageenan-producing seaweeds. K. striatum is also a source of iota carrageenan. The study was aimed to evaluate the effects of extraction time and alkali concentration on the characteristics of semi refined carrageenan (SRC) produced from seaweeds K. striatum and K. alvarezii. The SRC was extracted prepared by cooking dried seaweed samples in KOH solution (ratio seaweed:KOH solution= 1:40) with KOH concentrations of 6, 8 and 10% for 60 and 120 minutes at 70°C. The results showed that the best SRC characteristics produced from K. striatum seaweed were obtained from the extraction process at 6% KOH for 60 minutes which yielded 46.05±0.16%, carrageenan with gel strength of 362,07±21,44 g/cm2 and viscosity at 70°C 74 cP. Meanwhile the best characteristics of SRC produced from K. alvarezii seaweed were obtained from extraction in 10% KOH for 60 minutes having the highest yield of 39,03±0.95%, gel strength 1130.67± 16.34 g/cm2 and viscosity at 70°C of 59 cP. FTIR analysis showed that the functional groups which are kappa carrageenan and iota carrageenan characteristics were found in both samples at wave numbers of 846.97-847.09 and 800.53-801.29 cm-1, respectively.